2017
DOI: 10.4236/as.2017.84020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Growth Stimulants on Alfalfa Response to Salt Stress

Abstract: Salinity is a major impediment to crop production. This study was undertaken to compare the effect of seaweed extract, humic acid, and potassium sulfate nanoparticles in alleviating salt stress in Alfalfa (Medicago sativa L.). Seeds of ten alfalfa genotypes were germinated in a growth chamber at five salt concentrations (0%, 0.5%, 1.0%, 1.5%, and 2.00%). Salt concentrations above 1% reduced seed germination by more than 70% in most genotypes. One salt tolerant genotype (Mesa-Sirsa) and one salt sensitive (Bull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
1
14
1
Order By: Relevance
“…Our results contrast with those of Pettit (2004), who stated that humic substances neutralize pH. In soils affected by salts, there might be a reduction in pH and not a neutralization, accompanied by a reduction of fertility in the presence of humic substances (especially those with more humic acid concentration), a fact also recently observed by another research (El‐Sharkawy et al, 2017).…”
Section: Resultscontrasting
confidence: 99%
“…Our results contrast with those of Pettit (2004), who stated that humic substances neutralize pH. In soils affected by salts, there might be a reduction in pH and not a neutralization, accompanied by a reduction of fertility in the presence of humic substances (especially those with more humic acid concentration), a fact also recently observed by another research (El‐Sharkawy et al, 2017).…”
Section: Resultscontrasting
confidence: 99%
“…The work of El-Sharkawy et al (2017) on seaweed extracts highlighted the improvement of the alfalfa response to salinity stress, this improvement resulted in a decrease in electrolyte leakage; these same authors showed that high saline concentrations significantly increase electrolyte leakage compared to the control (non-saline).…”
Section: Discussionmentioning
confidence: 97%
“…These studies especially focus on the mechanisms of these microorganisms in root development and nodulation but pay little attention to the plant architecture and leaf morphology. A few studies exist on plant growth stimulating seaweed extracts applied under normal [36] and salt stressed [35] conditions. However, no study has used living green microalgae cells for growth stimulation of legumes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they sequester carbon, which makes them promising candidates for fuelwood. Although most studies on legumes focus on their interaction with plant-growth-promoting rhizobacteria (PGPR), a few studies evaluate the effect of seaweed and MA biostimulants on these plants including Phaseolus vulgaris [7,30], Vigna radiata [6,31,32], Glycine max [33,34] and Medicago sativa [35][36][37]. In plant biostimulant studies, MA were administered to plants in the form of extracts [32,[38][39][40], dry biomass [41][42][43][44][45], spent medium/supernatant [46,47], whole cultures [46] as well as cell suspensions [47,48], and desirable results were achieved.…”
Section: Introductionmentioning
confidence: 99%